Does religion affect motivation and job satisfaction in academia? A case study from Norway and France - Anatoliy Goncharuk; Jan Inge Jenssen; Didier Vinot (Problems and Perspectives in Management)
Religious affiliation is one of the indicators of the internal personality and spirituality of an employee. Although it can increase organizational effectiveness through motivation and job satisfaction, managers have not yet implemented this indicator in their work for various reasons. The purpose of this study is to test whether religious affiliation has a significant effect on the motivation and job satisfaction of faculty members at management schools in Norwegian and French higher education institutions. A survey of 96 academic workers was conducted in the spring of 2023. The results were examined using a one-way ANOVA test. The findings revealed a significant disparity in motivation and job satisfaction among academics of different religious affiliations. Only 10% of the considered motivators turned out to be significantly equal for all surveyed academic workers, while the majority showed a significant difference. Representatives of Western religions and atheists in general are significantly less motivated and satisfied with their work than representatives of Eastern religions. Significant differences were also found between representatives of various Eastern religions, indicating the impact of religion on the motivation and job satisfaction of academic workers. These findings provide an opportunity for university management to better motivate and satisfy academic staff based on their religious affiliations. When forming the teams to perform work tasks, managers can consider these findings to achieve better interaction and quality and improve organizational effectiveness.